Neurodegenerative Disease and the NLRP3 Inflammasome - Holbrook, Jonathan A.; Jarosz-Griffiths, Heledd H.; Caseley, Emily; Lara-Reyna, Samuel; Poulter, James A.; Williams-Gray, Caroline H.; Peckham, Daniel; McDermott, Michael F. (Frontiers in Pharmacology, 2021)
The prevalence of neurodegenerative disease has increased significantly in recent years, and with a rapidly ageing global population, this trend is expected to continue. These diseases are characterised by a progressive neuronal loss in the brain or peripheral nervous system, and generally involve protein aggregation, as well as metabolic abnormalities and immune dysregulation. Although the vast majority of neurodegeneration is idiopathic, there are many known genetic and environmental triggers. In the past decade, research exploring low-grade systemic inflammation and its impact on the development and progression of neurodegenerative disease has increased. A particular research focus has been whether systemic inflammation arises only as a secondary effect of disease or is also a cause of pathology. The inflammasomes, and more specifically the NLRP3 inflammasome, a crucial component of the innate immune system, is usually activated in response to infection or tissue damage. Dysregulation of the NLRP3 inflammasome has been implicated in the progression of several neurodegenerative disorders, such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and prion diseases. This review aims to summarise current literature on the role of the NLRP3 inflammasome in the pathogenesis of neurodegenerative diseases, and recent work investigating NLRP3 inflammasome inhibition as a potential future therapy.